Assessing Diversity in the Camelina Genus Provides Insights into the Genome Structure of Camelina sativa. Issue 4 (1st April 2020) - Chaudhary, Raju; Koh, Chu Shin; Kagale, Sateesh; Tang, Lily; Wu, Siu Wah; Lv, Zhenling; Mason, Annaliese S; Sharpe, Andrew G; Diederichsen, Axel; Parkin, Isobel A P
Abstract: Camelina sativa (L.) Crantz an oilseed crop of the Brassicaceae family is gaining attention due to its potential as a source of high value oil for food, feed or fuel. The hexaploid domesticated C. sativa has limited genetic diversity, encouraging the exploration of related species for novel allelic variation for traits of interest. The current study utilized genotyping by sequencing to characterize 193 Camelina accessions belonging to seven different species collected primarily from the Ukrainian-Russian region and Eastern Europe. Population analyses among Camelina accessions with a 2n = 40 karyotype identified three subpopulations, two composed of domesticated C. sativa and one of C. microcarpa species. Winter type Camelina lines were identified as admixtures of C. sativa and C. microcarpa . Eighteen genotypes of related C. microcarpa unexpectedly shared only two subgenomes with C. sativa, suggesting a novel or cryptic sub-species of C. microcarpa with 19 haploid chromosomes. One C. microcarpa accession (2n = 26) was found to comprise the first two subgenomes of C. sativa suggesting a tetraploid structure. The defined chromosome series among C. microcarpa germplasm, including the newly designated C. neglecta diploid née C. microcarpa, suggested an evolutionary trajectory for the formation of the C. sativa hexaploid genome and re-defined the underlying subgenome structure of the reference genome.